Confocal microscopy methods and protocols - Paddock, Stephen W (Humana Press, 1999)
Univ. of Wisconsin, Madison. Discusses the use of confocal techniques, imaging processes, and writing research. For researchers.
Methods in molecular biology ; vol. 122
Keywords: klinické laboratorní techniky; Clinical Laboratory Techniques; konfokální mikroskopie; Microscopy, Confocal; chemie, klinická chemie